Research orientation among general practitioners compared to other specialties - Markku Sumanen; Tiia Reho; Teppo Heikkilä; Pekka Mäntyselkä; Hannu Halila; Kari Mattila (Taylor & Francis Group, 2021)
Objective The volume of research work done by general practitioners (GP) is modest compared to other specialties. In order to find out reasons for this we examined the current situation concerning research orientation and factors relating to them among Finnish GPs compared to other specialists. Design and setting Data from The Physician 2018 Study were used for our research. The study was undertaken in collaboration with all five medical faculties in Finland and the Finnish Medical Association. It compiled information on physicians` social background, work history and career and research plans as well as their views regarding undergraduate and specialist training, values, and professional identity. Subjects The basic study population comprised all Finnish doctors under 70 years of age (N = 23,131). Questionnaires were sent to doctors born on even-numbered days (n = 11,336). Altogether 5,214 (45.8%) responded. Responses from GPs (n = 796) were compared with those of doctors in other specialties (n = 3,514). Main outcome measures and results The respondents were asked about their current intention to undertake a doctoral degree. Factors associated with this were analysed. Only 7.3% of GPs had completed a doctoral degree. The corresponding figure in other specialties was 32.3% (p < 0.001). In general practice the current intention to undertake a doctoral degree had only slightly increased over ten years. Most GPs had also decided not to undertake a doctorate. The main factors associated with the current intention to complete a doctoral degree were interest in attaining a senior position (OR 3.43, 95% CI 2.25-5.24), a position in a university hospital district (OR 2.89, 95% CI 1.69-4.94) or other sector than primary care (OR 1.87, 95% CI 1.18-2.96), one's father being a doctor (OR 2.01, 95% CI 1.09-3.72) and male gender (OR 1.63, 95% CI 1.05-2.54). Conclusion Research work in primary health care has been quite sparse. In general practice there is a need to increase teaching and guidance in research work.Key points Research work in primary health care is not very common. Only 7.3% of GPs had completed their doctorate compared to 32.3% in other specialties. A main factor associated with the current intention to complete a doctoral degree was interest in attaining a senior position.